False Positive Results in SARS-CoV-2 Serological Tests for Samples From Patients With Chronic Inflammatory Diseases - Kharlamova, Nastya; Dunn, Nicky; Bedri, Sahl K.; Jerling, Svante; Almgren, Malin; Faustini, Francesca; Gunnarsson, Iva; Rönnelid, Johan; Pullerits, Rille; Gjertsson, Inger; Lundberg, Karin; Månberg, Anna; et al. (Frontiers in Immunology, 2021)
Patients with chronic inflammatory diseases are often treated with immunosuppressants and therefore are of particular concern during the SARS-CoV-2 pandemic. Serological tests will improve our understanding of the infection and immunity in this population, unless the tests give false positive results. The aim of this study was to evaluate the specificity of SARS-Cov-2 serological assays using samples from patients with chronic inflammatory diseases collected prior to April 2019, thus defined as negative. Samples from patients with multiple sclerosis (MS, n=10), rheumatoid arthritis (RA, n=47) with or without rheumatoid factor (RF) and/or anti-cyclic citrullinated peptide antibodies (anti-CCP2) and systemic lupus erythematosus (SLE, n=10) with or without RF, were analysed for SARS-CoV-2 antibodies using 17 commercially available lateral flow assays (LFA), two ELISA kits and one in-house developed IgG multiplex bead-based assay. Six LFA and the in-house validated IgG assay correctly produced negative results for all samples. However, the majority of assays (n=13), gave false positive signal for samples from patients with RA and SLE. This was most notable in samples from RF positive RA patients. No false positive samples were detected in any assay using samples from patients with MS. Poor specificity of commercial serological assays could possibly be due to interfering antibodies in samples from patients with chronic inflammatory diseases. For these patients, the risk of false positivity should be considered when interpreting results of the SARS-CoV-2 serological assays.